Penggunaan Vasokonstriktor dalam Anestesi Lokal Kedokteran Gigi pada Pasien Kompromis Medis: Telaah Pustaka - Dwi Riski Saputra; Iga Putri Imansari; Aulia Rahma Elnisa; Hanifah Nailul Amania (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Vasoconstrictors are commonly used with local anesthetics to control pain in dental practice. This is related to the role of vasoconstrictors in the alpha 1 receptor smooth muscle of peripheral blood vessels. Vasoconstrictors are able to constrict peripheral blood vessels in the area around the injection site, so that there is a decrease in absorption of local anesthetic drugs in tissue. These conditions also contribute to the prolongation of the duration of action, the depth of anesthesia and the systemic reduction in drug toxicity. The aim of study to assess the recent vasoconstrictor that used in dentistry. Vasoconstrictors in local anasthesia can constrict peripheral blood vessels and have a negative effect on the vicinity of the injection site. These negative effects include prolongation of the bleeding process after surgery and inhibition of the wound healing process. Negative effects of vasoconstrictors are also associated with vasoconstrictor interactions with other types of drugs in dental practice. The use of vasoconstrictors can be very dangerous for patients with a history of cardiovascular disease such as unstable angina, ventricular tachycardia, fibrilar tachycardia and others. Understanding of vasoconstrictor pharmacology, vasoconstrictor interactions with other drugs, clinical use and contraindications to vasoconstrictor use are very important.